Demand for public events in the COVID-19 pandemic: a case study of European football. Issue 3 (27th May 2021) - Reade, J. James; Singleton, Carl
ABSTRACT: Research question: This study looks at stadium attendances in elite-level European football, to suggest how people responded to the initial COVID-19 outbreak. This offers insight into how professional sports will emerge from social lockdowns and competition taking place behind closed doors. Research methods: The analysis focuses on the top leagues of England, Italy, France, Spain and Germany. Using panel data methods and exploiting the variation in day-to-day attendances in these leagues, the impacts on implied spectator demand from the news of confirmed COVID-19 cases and deaths can be quantified. Results and Findings: In Italy, England and Germany, stadium attendances were negatively affected by the previous day's newly confirmed domestic cases or deaths. In Spain and France, there was no attendance response to the early stages of the domestic outbreaks. Implications: COVID-19 was affecting football match spectator demand before European countries enforced lockdowns and other restrictions to suppress the spread of the disease. This suggests that fans significantly responded to the risk of catching the virus. If this risk remains when stadiums reopen, then sports organisations should expect reduced ticket demand. This suggests that managers should adopt more dynamic and creative pricing strategies, and use their stadiums in more innovative ways, if they are to survive financially in a world where COVID-19 remains a threat to public health.